KEPERCAYAAN DIRI DALAM BELAJAR PADA MAHASISWA YANG SUDAH BEKERJA DAN YANG BELUM BEKERJA - Harahap, Juli Yanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine differences in self-confidence in learning among students who are already working and who are not yet working. Confidence is something that guides students in learning, so that communication and confidence are interconnected. But the reality that occurs from the results of the hypothesis in this study, which is seen in the classroom that in terms of self-confidence there is no difference between students who work and those who have not worked, this is due to the results of self-confidence scale between students who work and Not working together is the same, so they are confident in receiving learning in class. Data collection was carried out in this study using a confidence scale by administering questionnaires to a sample of 40 students. Data analysis method used in this study is a regression test using the Pearson Product Moment formula.